2002
DOI: 10.1116/1.1502698
|View full text |Cite
|
Sign up to set email alerts
|

Formation and removal of composite halogenated silicon oxide and fluorocarbon films deposited on chamber walls during plasma etching of multiple film stacks

Abstract: Articles you may be interested inEvolution of titanium residue on the walls of a plasma-etching reactor and its effect on the polysilicon etching rate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(84 citation statements)
references
References 14 publications
5
76
0
Order By: Relevance
“…Rf capacitive discharge in SF 6 is widely applied in technological processes of etching silicon-based materials [2,3], GaAs [4], treatment of polyethylene films [5] and textile [6], cleaning walls of technological vessels from etching or deposition products [7], etc. Therefore a large number of papers are devoted to studying rf discharge in SF 6 both in experiment and in theory.…”
Section: Introductionmentioning
confidence: 99%
“…Rf capacitive discharge in SF 6 is widely applied in technological processes of etching silicon-based materials [2,3], GaAs [4], treatment of polyethylene films [5] and textile [6], cleaning walls of technological vessels from etching or deposition products [7], etc. Therefore a large number of papers are devoted to studying rf discharge in SF 6 both in experiment and in theory.…”
Section: Introductionmentioning
confidence: 99%
“…The small peak at 973 cm −1 is not observed in a similar experiment by Ullal et al [12]. The closest candidate is the Si-OH stretching mode at 980 cm −1 referred in Lang et al [17].…”
Section: A Analysis Of the Deposition Film On The Chamber Wallmentioning
confidence: 73%
“…In the model, it is assumed that the deposition rate is proportional to oxygen flow rate although no experimental data is provided. In the further studies about SF 6 plasma cleaning, they confirmed that fluorination of the OSi-Cl layer propels the cleaning process [13,14].…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations